Characterization of myeloid leukocytes and soluble mediators in pancreatic cancer: importance of myeloid-derived suppressor cells - Karakhanova, Svetlana; Link, Julia; Heinrich, Moritz; Shevchenko, Ivan; Yang, Yuhui; Hassenpflug, Matthias; Ahn, Katharina von; Maier, Caroline; Umansky, Viktor; Werner, Jens; Bazhin, Alexandr V. (OncoImmunology, 2015)
Pancreatic ductal adenocarcinoma (PDAC) represents one of the deadliest cancers in the world. PDAC cells activate tumor-specific immune responses but simultaneously trigger a strong immunosuppression. We showed that PDAC cells produce high amount of chronic inflammatory mediators and PDAC tumors build an immunosuppressive cytokine milieu, which correlates with tumor progression. We observed a low frequency of dendritic cells (DC) and a pronounced accumulation of macrophages and myeloid-derived suppressor cells (MDSC) in murine PDAC tumors. A strong accumulation of MDSC has also been demonstrated in the peripheral blood of resected PDAC patients. While DC and macrophages seem not to play a significant role in this PDAC model in the context of immunosuppression, MDSC are highly suppressive, and their accumulation is associated with an increase in intratumoral VEGF concentration during the PDAC progression. Application of the phosphodiesterase-5 inhibitor sildenafil led to a prolonged survival of PDAC-bearing female mice, which was due to the decrease in MDSC frequencies and in the systemic VEGF level. This led to a restoration of anticancer immune responses, manifested in the recovery of T lymphocyte functions and in an increase in the frequency of conventional CD4+ T cells in tumors and IFNγ level in serum of PDAC-bearing mice. Thus, MDSC are strongly involved in the PDAC-associated immunosuppression and that their depletion could create new approaches for therapy of PDAC.